Silica Nanoflowers-Stabilized Pickering Emulsion as a Robust Biocatalysis Platform for Enzymatic Production of Biodiesel - Lihui Wang; Xinlong Liu; Yanjun Jiang; Peng Liu; Liya Zhou; Li Ma; Ying He; Heyu Li; Jing Gao (Catalysts, 2019)
Enzymatic production of biodiesel had attracted much attention due to its high efficiency, mild conditions and environmental protection. However, the high cost of enzyme, poor solubility of methanol in oil and adsorption of glycerol onto the enzyme limited the popularization of the process. To address these problems, we developed a silica nanoflowers-stabilized Pickering emulsion as a biocatalysis platform with Candida antarctica lipase B (CALB) as model lipase for biodiesel production. Silica nanoflowers (SNFs) were synthesized in microemulsion and served as a carrier for CALB immobilization and then used as an emulsifier for constructing Pickering emulsion. The structure of SNFs and the biocatalytic Pickering emulsion (CALB@SNFs-PE) were characterized in detail. Experimental data about the methanolysis of waste oil to biodiesel was evaluated by response surface methodology. The highest experimental yield of 98.5 ± 0.5% was obtained under the optimized conditions: methanol/oil ratio of 2.63:1, a temperature of 45.97 °C, CALB@SNFs dosage of 33.24 mg and time of 8.11 h, which was closed to the predicted value (100.00%). Reusability test showed that CALB@SNFs-PE could retain 76.68% of its initial biodiesel yield after 15 cycles, which was better than that of free CALB and N435.